A budget analysis of different soil fertility treatments for conventional and organic vegetable farming on a smallholding in South Africa - Sithole, Philemon Gwinyai (Stellenbosch : Stellenbosch University, 2018)
Thesis (MCom)--Stellenbosch University, 2018.